The Communist Manifesto and the Fatherland: on the Development of the National Question in young Marx - Matković, Aleksandar (Napredak, 2023)
The 175th anniversary of the publication of the Communist Manifesto passed unnoticed recently. In order to contribute to the anniversary in the spirit of a scholarly discussion, this article begins a forgotten topic – Marx’s consideration of nationalism and national struggles. Through the analysis of the Manifesto and Marx’s and Engels’ political articles, the author presents new elements of Marx’s theory of the nation, which rested on the difference between progressive and regressive struggles: those that led to greater democratization of society through the inclusion of the proletariat and those that opposed it. The criticism of young Marx is presented at the end, along with the contribution he can make today.
Keywords: Communist Manifesto; Engels; fatherland; Marx; nation; national struggles